EFEKTIVITAS SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DINAS PERHUBUNGAN KOTA SURABAYA - Heru Irianto; Susi Ratnawati; Feby Suryaning Tyas (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
This study aims to provide information about the effectiveness of the personnel management information system at the Surabaya City Transportation Service. The benefits of this management information system research aim to make it easier for employees to find information about personal data. And with the management information system, work becomes more effective and efficient. The research method used is a qualitative research type. The data collection techniques used in this research are interviews and documentation, the researcher will examine the object of his study by holding direct interactions with informants. The focus of the research used in this study is how the effectiveness of the Surabaya Transportation Agency's personnel management information system is analyzed using 2 variables to measure the effectiveness of the management information system, namely innovative applications and information resources. The research location which is the place for the author to conduct research is the Surabaya City Transportation Service. The results showed that the Management Information System is very important for the employees of the Surabaya City Transportation Service because the work becomes more effective and efficient. Keywords: Effectiveness, System, Information, Management, Personnel.